Evaluación de la fitorremediación como técnica de recuperación ambiental de relaves auríferos en la costa sur del Perú - Castillón Hilario, Flor Angel (2025)
Gold mining on the southern coast of Peru generates tailings contamination, most of which has not been characterized due to informal management. However, some contain recoverable Au and Ag grades. A representative sample yielded 1.72 g Au/t and 31.76 g Ag/t, and arsenic, copper, and lead concentrations of 340.73, 15.33, and 110 mg/kg, respectively. Optical microscopy revealed the presence of electrum, with gold and silver, 38.46% in free form. To recover the metals, leaching with Sandioss was applied, obtaining 45.86% gold and 90.17% silver recoveries in 24 hours, with a consumption of 5.15 kg/t of the reagent. The tailings were subsequently subjected to phytoremediation with aloe vera, prickly pear, casuarina, geranium, tara, and ant plant. After six months, only Caesalpina spinosa (tara) adapted to the environment. It absorbed 17.11% of arsenic in its roots and 15.45% in its shoots. Regarding copper, tara showed a greater capacity for copper assimilation, with 41.46% in its roots and 26.22% in its shoots. Lead absorption was 10.15% in its roots and 25.4% in its shoots, demonstrating the effectiveness of tara as a phytoremediation species in soils contaminated by tailings.